Circular Economy in Tourism – Economic Challenges and Perspectives for Sustainable Development - Stanoeva, Lilly (Research Papers, 2025)
This study examines the opportunities and challenges of implementing the circular economy in tourism, highlighting its role in sustainable development, resource efficiency and waste reduction. It focuses on the economic barriers faced by tourism businesses in Bulgaria, including financial constraints, lack of infrastructure and low awareness. The importance of sustainable certifications such as “Green Key” and “Green Lodge” as a tool to promote responsible practices is also analyzed. As a recommendation for future research, an empirical study through semi-structured interviews with representatives of the tourism sector is proposed to identify the real challenges and the extent of implementation of circular models in the country. The proposed methodology has the potential to support the formulation of more effective policies and business strategies tailored to the Bulgarian context of sustainable development.